Labour market skills, endogenous productivity and business cycles - Mirko Abbritti; Agostino Consolo (European Central Bank (ECB), 2022)
This paper analyses how labour market heterogeneity affects unemployment, productivity and business cycle dynamics that are relevant for monetary policy. The model matches remarkably well the short and long run dynamics of skilled and unskilled workers. Skill mismatch and skill-specific labour market institutions have three main effects on business cycles and growth dynamics. First, as the composition of labour market skills leads to supply segmentation, the relative scarcity of skilled workers increases the natural rate of unemployment and reduces total factor productivity with long- run effects on the growth rate of output. Second, skill heterogeneity in the labour market generates asymmetric outcomes and amplifies measures of employment, wages and consumption inequality. Finally, the model provides important insights for the Phillips and Beveridge curves. Skill-specific labour market heterogeneity leads to a flattening of the Phillips curve as wages and unemployment are affected differently across skill types. Also, the model generates sideward shifts of the Beveridge curve following business cycle shocks that are related to the degree of skill heterogeneity.
Keywords: E24; E3; E5; O41; J64; 330; Monetary policy; labour market; skill heterogeneity; endogenous growth; unemployment fluctuations; Phillips curve; Beveridge curve; consumption inequality